Legal Status and Protection for Women Human Rights Defenders in Indonesia - Niken Savitri; Dyan Franciska Dumaris Sitanggang (Universitas Lampung, 2022)
The term Human Rights Defenders (Pembela HAM in Indonesia) stands for any people or group whose activities revolve around the defense and promotion of human rights and other basic freedoms. In the course of their work, human rights defenders often experience verbal threats, attacks and even physical acts of violence that seriously hamper their activities.Women human rights defenders are an important part of human rights activism. However, they are a vulnerable group because of their position and status as women. Being vulnerable, the bodies, sexuality and identity of women human rights defenders have been violently attacked through the exploitation of gender stereotypes biased against women. However, it is apparent that women human rights defenders in Indonesia are not adequately protected. This paper employs normative analytical descriptive research methods by looking at the specificity of women human rights defenders as a vulnerable group facing specific attacks and violence, as well as examining various norms of protection. The Government of Indonesia through the existing legal norms has an obligation to fulfil the protection of women human rights defender, considering the vulnerability of women human rights defenders.